2016
DOI: 10.1039/c6ra15186h
|View full text |Cite
|
Sign up to set email alerts
|

Ag(i), Cu(ii), Co(iii) and Hg(ii) complexes and metal-assisted products derived from 4-methyl-piperidine-carbodithioate: syntheses, structures, thermal analyses, redox behaviour and fluorescence properties

Abstract: Ag(i), Cu(ii), Co(iii) and Hg(ii) complexes and metal-assisted products derived from 4-methyl piperidine have been synthesized. The Cu(ii) complex is redox reversible and compounds3and5are fluorescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…This complexity was attributed to intraligand SÁ Á ÁH interactions involving the tertiary hydrogen of the ISSN 2056-9890 isobutyl group. Although the room temperature 1 H NMR spectrum of N,N,N 0 ,N 0 -tetrakis(2-methylpropyl)thioperoxydicarbonic diamide (tetraisobutylthiuram disulfide) itself does not show evidence of such intramolecular interaction, several recent studies of tetrathiuram disulfides have suggested such interactions in the crystalline state (Raya et al, 2005;Srinivasan et al, 2012;Nath et al, 2016). This possibility of similar weak interaction(s) in the crystal structure of tetraisobutylthiuram disulfide has motivated a determination of its structure by X-ray diffraction, reported herein.…”
Section: Chemical Contextmentioning
confidence: 88%
See 1 more Smart Citation
“…This complexity was attributed to intraligand SÁ Á ÁH interactions involving the tertiary hydrogen of the ISSN 2056-9890 isobutyl group. Although the room temperature 1 H NMR spectrum of N,N,N 0 ,N 0 -tetrakis(2-methylpropyl)thioperoxydicarbonic diamide (tetraisobutylthiuram disulfide) itself does not show evidence of such intramolecular interaction, several recent studies of tetrathiuram disulfides have suggested such interactions in the crystalline state (Raya et al, 2005;Srinivasan et al, 2012;Nath et al, 2016). This possibility of similar weak interaction(s) in the crystal structure of tetraisobutylthiuram disulfide has motivated a determination of its structure by X-ray diffraction, reported herein.…”
Section: Chemical Contextmentioning
confidence: 88%
“…Values for and for structures in the Cambridge Structural Database (Web CSD v1.1.1; Groom et al, 2016) were determined using Mercury (Macrae et al, 2008). These structures are: METHUS (Marøy, 1965), METHUS01 (Ymé n, 1983), METHUS02 (Wang et al, 1986), METHUS03 (Wang & Liao, 1989), METHUS04 (Wang & Liao, 1989), ETHUSS (Karle et al, 1967) ETHUSS01 (Wang et al, 1986), ETHUSS02 (Wang & Liao, 1989), ETHUSS03 (Wang & Liao, 1989), ETHUSS04 (Shi & Wang, 1992), ETHUSS05 (Hu, 2000), HIQJUM (Jian et al, 1999), HIQJUM01 (Yu & Wang, 2003), JECYAZ (Kumar et al, 1990), TIBFEQ (Zhai et al, 2007), ZEMPUC (Hall & Tiekink, 1995), KAZHEA (Karim et al, 2012), NELTUT (Fun et al, 2001), XEBJOF (Ajibade et al, 2012), JAXPOO (Raya et al, 2005), CAPLEK (Williams et al, 1983), CAPLEK01 (Ymé n, 1983), CAPLEK02 (Yamin et al, 1996), CAPLEK03 (Bai et al, 2010), RISNEN (Quan et al, 2008), ULOXIC (Bodige & Watson, 2003), PIPTHS (Dix & Rae, 1973), PIPTHS01 (Shi & Wang, 1992), EWESUW (Nath et al, 2016), BOMPAU (Rout et al, 1982), VOHFIH (Polyakova & Starikova, 1990), VOHFIH01 (Ivanov et al, 2003), PECWOL…”
Section: Database Surveymentioning
confidence: 99%
“…2,3-dimercaptopropanol (British Anti-Lewisite) are used as antidotes in cases of mercury poisoning (Canty & Kishimoto, 1975). 4-Methyl-piperidinecarbodithioate forms a linear mercury(II) complex in which the dithiosulfur atom coordinates to the mercury(II) ion (Nath et al, 2016;Dar et al, 2015) while in the present work the benzyl ester undergoes cleavage and a sulfur atom from the benzyl mercapto moiety of the ligand coordinates to the mercury(II) cation ( Fig. 1).…”
Section: Structure Descriptionmentioning
confidence: 71%
“…Organomercury(II) cations have a high affinity for bonding through the sulfur donor sites present in amino acids, peptides and proteins (Clarkson & Magos, 2006;Hoffmeyer et al, 2006;Rooney, 2007). Crystal structures of several phenylmercury(II) complexes with Hg-S bonds and strong intermolecular HgÁ Á ÁS interactions have been reported (Yadav et al, 2014;Bharti et al, 2013;Nath et al, 2016). Mercury has long been used in medicine and industry which has caused toxicity problems.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Dithiocarbamates have attracted attention as readily accessible and structurally changeable ligands for transition metal ions and have even found manifold practical use [6][7][8]. [9][10][11][12][13] or even to mononuclear complexes of the type [(R 3 P) 2 Ag(S 2 CNR 2 -κ 2 S,S′)] [10,14,15], depending on the amount and type of the auxiliary ligand.…”
Section: Commentmentioning
confidence: 99%